América latina frente a la crisis económica internacional : buena resistencia global y diversidad de situaciones nacionales - Carlos Quenan (IdeAs)
The Latin American region held up well during the first phase of the international economic crisis started in 2007. During the period of worsening of the crisis, after the collapse of Lehman Brothers, Latin American countries did not know any monetary or financial crisis and experimented a mild recession because the recovery was strong in 2010. This degree of resilience is explained to a large extent by the decrease of financial vulnerability during the phase of growth expansion (2003-2008).However, beyond the common features to the region as a whole, the crisis has exposed a wide range of national situations. The factors that lie behind these differences are related to the magnitude of the unfavourable shocks affecting each economy, the degree of diversification of the external economic relations and the manoeuvring room of each country to implement counter-cyclical measures. This helps to distinguish the cases of Mexico and Venezuela, heavily affected in 2009, compared with those of Bolivia or Brazil, which held up well during the first phase of the international economic crisis. Nevertheless, even the countries whose growth regimes may have mitigated the unfavourable effects of the adverse shocks suffered serious challenges.